Linear assembly of hexadecanethiol coated gold nanoparticles - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2008)
An interesting formation of linear assembly of hexadecanethiol coated gold nanoparticles is demonstrated. The nanoparticles used were synthesized in an organic medium and then were subjected to digestive ripening to finally yield monodisperse nanoparticles. A simple drop casting on TEM grid lead to the results observed. Based on the thermo gravimetric analysis, it is hypothesized that inclusion of the particles in Au(I)-thiolate template is mainly responsible for the formation of linear assembly. (c) 2008 Elsevier B.V. All rights reserved.

Static and dynamic magnetic properties of Co nanoparticles - Srinath, S.; Poddar, P.; Sidhaye, Deepti S.; Bhagavatula L. V. Prasad; Gass, James; Srikanth, H. (Journal of Nanoscience and Nanotechnology, 2008)
Co nanoparticles have been synthesized using wet-chemical methods. As-synthesized particles show a sharp low temperature peak in zero-field cooled (ZFC) magnetization well below the blocking transition temperature and this feature is associated with surface spin disorder. We have investigated the dynamic magnetic properties of Co using ac susceptibility and resonant RF transverse susceptibility (TS). We also studied the memory and relaxation effects in these nanoparticle systems. From these measurements we show a typical blocking behavior of an assembly of superparamagnetic nanoparticles with a wide distribution of blocking temperatures. The transverse susceptibility measurements on these particles show the presence of anisotropy even above the blocking temperature. The role of surface anisotropy and the size distribution of the particles on the observed memory and magnetic relaxation effects are discussed.
International Conference on Advanced Nano-Materials, Indian Inst Technol, Phys Dept, Bombay, INDIA, JAN 08-10, 2007
Keywords: Ac Susceptibility; Co Nanoparticles; Magnetic relaxation; Transverse Susceptibility

Preparation of nearly monodisperse nickel nanoparticles by a facile solution based methodology and their ordered assemblies - Sidhaye, Deepti S.; Bala, Tanushree; Srinath, S.; Srikanth, H.; Poddar, Pankaj; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2009)
Nickel nanoparticles have been synthesized by a simple wet chemical reduction technique in the presence of a surfactant sodium dodecyl sulfate (SDS) and a capping agent oleic acid. Varying the concentration of the surfactant and the capping agent has been found to critically govern the nature of the nanoparticles prepared. It is observed that at an optimum concentration of SDS and oleic acid, nearly monodisperse Ni nanoparticles are obtained that form highly ordered hexagonally close-packed structures on electron microscopy grids by a simple drop coating procedure. It is also shown that the presence of oleic acid is necessary for the stability of the Ni nanoparticles synthesized. Structural and magnetic characterizations of the nanoparticles are also presented.

Melting characteristics of superlattices of alkanethiol-capped gold nanoparticles: the ``excluded'' story of excess thiol - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemistry of Materials, 2010)
Melting characteristics of gold nanoparticle superlattices obtained from nanoparticles capped by alkanethiols of different chain lengths (octane, dodecane and hexadecane) have been investigated. The alkanethrol capped nanoparticles were synthesized by the well-established digestive ripening method It is observed that as the chain length Of the thiol increases, the propensity to form superlattices decreases and the melting of the superlattice is observed at lower temperature However, the Formation of the 3D superlattice is critically dependent on the presence of ``excess'' thiol as determined from thermogravimetric and transmission electron microscope analysis. In the absence of ``excess'' thiol, only 2D hexagonally close-packed arrangements were seen

Many manifestations of digestive ripening: monodispersity, superlattices and nanomachining - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2011)
Digestive ripening has now been established as a very convenient route to obtain monodisperse nanoparticles from polydisperse ones by refluxing the latter in the presence of an excess ligand. Many ligands including long chain thiols, amines, or phosphines have been shown to be effective digestive ripening agents. It is hypothesized that the surface active groups of such digestive ripening agents bind and remove reactive surface atoms/clusters from big nanoparticles and redeposit them on smaller nanoparticles. In this way, large particles become smaller, while small particles become larger, and eventually, an equilibrium size is obtained that is specific to each of the digestive ripening agents used. Herein, the digestive ripening procedure is reviewed, discussed and its utility spanning the preparation of monodispersed metal nanoparticles, alloy nanoparticles, superlattice structures and the most interesting nano-machining (wherein the monodisperse particles can be reverted back to the polydisperse system) is demonstrated.

Digestive ripening: a fine chemical machining process on the nanoscale - Shimpi, Jayesh Ramesh; Sidhaye, Deepti S.; Prasad, Bhagavatula L V (Langmuir, 2017)
A comprehensive over view of the process named as 'digestive ripening' that is known to convert polydisperse nanocrystals to monodisperse ones is presented. Apart from highlighting the role of organic molecules (ligands) in achieving size control the role of other parameters like the nanocrystal-ligand binding strength and the temperature at which the reaction is carried out in accomplishing size control is also delineated. The generality of the procedure is illustrated by providing examples of how it is used to prepare monodispersed nanocrystals of different metals, alloy systems, ultra small nanocrystals and also to narrow the size distribution in complex binary and ternary nanocrystal systems. Finally, the current status as far as the theoretical understanding of how the size control is being achieved by digestive ripening is laid out, emphasizing at the same time the necessity to undertake more systematic studies to completely realize the full potential of this practically very useful procedure.